Gender Inequality: African Union Strategy to Combat Women Poverty Crisis in Somalia - Izzah Atirah Ruslan (Jurnal Hubungan Internasional, 2022)
Globalization has led to national security issues to occurred and resulted in people losing their fundamental human rights in some cases. Women’s poverty is clearly the deprivation of human rights for both women and young girls. Somalia, one of the nations in Africa regions, has suffered from the act of gender inequality that deprived the rights of women which led them to live in poverty. Social norms or traditions are playing a crucial role in worsening the condition of living hood among women in Somalia. While both men and women are indeed suffered poverty, however, men are getting wide chances to access job opportunities compared to women. However, in recent years, African Union has acknowledged the importance of women’s role in the economic development of the region, therefore African Union established the Gender Equality and Women’s Empowerment Strategy as a guide to both the government of the states and women’s agency to spread awareness regarding the rights of the women to be equal as men. Therefore, this paper further will discuss how successful such strategies are to be able to construct new ideas and social norms in Somalia.